Un enfoque no paramétrico para la descomposición de la productividad del trabajo en la industria manufacturera regional - Juan Carlos Chávez; Luis Fernando López Ornelas (Banco de México, 2013)
– This study decomposes both the labor productivity gap and the labor productivity growth into the contributions of technical efficiency, capital deepening and technological change for Mexican manufacturing at the regional level. In order to do so, we apply a methodology that combines two literatures: the nonparametric construction of production frontiers and the general decomposition approach developed by Shorrocks (2012) which is based on the Shapley value. The results indicate that regional differences in labor productivity are mainly attributed to technical efficiency, and, to a lesser extent, to regional differences in capital deepening. Moreover, labor productivity growth was not homogeneous across regions over the period 1998-2008. In both the north and the south, the increase in labor productivity was mainly driven by technical efficiency, while technological change was the most influential factor on labor productivity growth in the central regions.
Keywords: J24; L60; R1; 330; Capital intensity; Labor productivity; Technical efficiency; Technological change; Manufacturing; Shapley value